Thailand’s Policy and Law on Atmosphere Management for People’s Welfare: The Fight Against Climate Change - Peerapon Jaderojananont (Faculty of Law, Jambi University, 2018)
It is so true that climate change becomes the common concern of humankind which does not adversely affect any individual country only, but its effects also threaten the global community as a whole. As provided by international framework, climate change should be mitigated with the stabilization of greenhouse gas concentrations in the atmosphere at a safe and appropriate level. Although Thailand is not one of industrialized countries contributed to greenhouse gases emissions, it should take actions to cooperate with those countries to comply with such international framework. This article focuses on exploring and examining Thailand’s policy and law adopted to reduce greenhouse gases emissions in order to prove how Thailand is highly potential to comply and cooperate with the global community. This will reflect the substantial creation of low carbon society in Thailand where Thai people will be finally secured against the dangerous anthropogenic interference with the climate system.